Displaying Pirate Flags in Indonesia’s 80th Independence Celebrations: A Critical Discourse Analysis - Muntaha
The public display of the pirate’s “skull-and-crossbones” flag during Indonesia’s 80th Independence Day celebrations represent a visually and politically provocative departure from the conventional use of the national red-and-white emblem. This symbolic substitution not only challenges state-sanctioned rituals of commemoration but also invites scrutiny of how citizens negotiate meanings of nationalism in a shifting socio-political landscape. This study employs Critical Discourse Analysis (CDA) to explore the layered social meanings, power relations, and identity negotiations embedded in this act. Data were collected from news of online media reports, social media posts, and public commentary circulating between 15 July and 18 August 2025, capturing the period leading up to the official celebrations. The analysis focuses on three key dimensions: (1) the discursive framing of the pirate flag in news and social media; (2) the recontextualization of global pirate iconography within Indonesian socio-political debates; and (3) the role of digital platforms in amplifying and transforming the symbolic act into a broader site of ideological contestation. Findings reveal a deeply polarized interpretive field. Supporters frame the gesture as a creative and non-violent mode of resistance, drawing on humor, satire, and visual disruption to challenge dominant power structures; detractors view it as offensive, unpatriotic, and potentially destabilizing to national unity.